The Role of Competence in Nursing: A Cross‐Sectional Study Among Croatian Undergraduate and Graduate Students: Empirical Research Quantitative - Kata Ivanišević; Goran Hauser; Sandra Bošković (Nursing Open)
ABSTRACT Aim To assess the professional competencies of Croatian undergraduate and graduate nursing students using the Nurse Professional Competence (NPC) scale and to identify factors influencing these competencies. Design Cross‐sectional, correlational study. Methods The study was conducted between April and July 2022. A stratified random sample of 750 nursing students was selected from four higher education institutions in Croatia. The data was collected by means of an electronic survey using the Croatian language adapted version of the Nurse Professional Competence scale. The scale consists of 35 items in six domains, which are rated on a 7‐point Likert scale. Internal consistency was measured using Cronbach's α. The data were analysed using SPSS version 25, with both parametric and non‐parametric tests applied depending on the data distribution. Results A total of 750 nursing students with an average age of 31 years (SD = 10.54) participated in the study. The internal consistency of the six competency factors ranged from Cronbach's α = 0.75 (Medical and Technical Care) to α = 0.90 (Nursing Care, Care Pedagogics). The highest self‐assessed competence was in Value‐Based Nursing Care (M = 6.05, SD = 0.75) and the lowest in Medical and Technical Care (M = 4.96, SD = 0.88). Significant differences were found between the institutions in various areas of competence, with students at the University of Split achieving better results in several areas. Age and level of education were found to be significant predictors of competence in several areas. Patient or Public Contribution No input from patients or the public. This study focused solely on nursing students' self‐assessment in an educational setting.